PENGARUH PENGELUARAN PEMERINTAH, JUMLAH PENDUDUK DAN PENGANGGURAN TERHADAP KEMISKINAN DI KABUPATEN GRESIK - Mochammad Dewa Pratama Putra; Ririt Iriani Sri Setiawati (Promosi: Jurnal Program Studi Pendidikan Ekonomi, 2023)
This study use a quantitative research methodology. Using Gresik BPS data, this study wascarried out in Gresik Regency. The data collection procedure, however, is nearly identicalto this study and incorporates BPS data as well as relevant articles. The following variableswere used in this study: government spending (X1), population (X2), unemployment (X3),and poverty (Y). analysis of the data used in this study is Multiple Linear Regression witha significant level of 5%. The results showed that the government spending variable (X1)with a significant level (0.000) affected the poverty variable (Y). Population variable (X2)with a significant level (0.000) affects poverty variable(Y). While the unemploymentvariable (X3), with a significant level (0.176) does not affect the poverty variable (Y).Keywords: Government Expenditures, Total Population, Unemployment And Property